O mal e o sofrimento à luz da providência de Deus: enxergando benefícios na dor - Lima Neto, Manoel de Souza (2010)
Human suffering has permeated and challenged the theology and related sciences in an attempt to present a rational understanding of the problem of evil. The various religious denominations, theological and philosophical object are considered in this study in an attempt to condense a theoretical framework in the light of Scripture, is able to minimize the conflicts that arise from the challenge of reconciling the concept of a loving God with the unequivocal finding of human suffering. From a premise endorsed by the historic and Reformed theology that God makes all things happen in the world and in people's lives, this study aims to elucidate the question of evil and suffering, as well as presenting the potential benefits that suffering can provide the individual. Seeks to present a biblical argument that can contribute to respond to the problem of evil and suffering. Moreover, contextualizing the evil and suffering in God's plan. The various religious and philosophical attempts to give a plausible answer to the problem of suffering eventually create insurmountable barriers when faced with the Bible. Worldviews misconceptions about God are strong resistance in the Bible and contradict concepts solidified throughout the history of the church. Some of these worldviews have assumed prominence in theological discourse when the question of suffering is addressed. Although the more conservative discourse that sin is the cause of suffering he does not explain all forms of suffering, nor the Bible accepts sin as one reason for suffering. Can not see the suffering without regard for the ordeal. It is not intended to open space in this research to compare the different lines on the theological understanding of God's plan, but to present an understanding of how suffering fits into God's eternal plan.